Christian Teaching on Corruption: A Response of the Church to the Upsurge of Corruption in Ghana - Abraham Ofoe Agbenu; John Kwaku Opoku; Jonathan Edward Tetteh Kuwornu-Adjaottor (E-Journal of Religious and Theological Studies, 2025)
Corruption has been a major deterrent to the socioeconomic development of Ghana. Several anti-corruption measures have been initiated by the government to curb the menace from the time of the country’s independence till date. However, incremental surveys conducted and ratings on corruption in the last decade show a continuous escalation of the canker in the nation. Considering the high percentage of the Christian population (71.3%) in Ghana, the Christian Church becomes a key stakeholder in the affairs of the country. Therefore, the study examined the Biblical teachings on the act of corruption and the response of the Church to the problem in the quest of the nation to win the battle against corruption. From the study, it was discovered that the Bible frowns on the givers and receivers in the act of corruption and further cautions that corruption brings calamity to society, especially in the administration of justice. Similarly, the Church in Ghana has condemned the involvement of citizens in the act of corruption. Christian leaders have further proposed the need for the State to establish anti-corruption policies and prosecute persons found guilty of the act. However, the key role that the Church is playing in this quest is still not clear. The study, therefore, recommended the need for the various Christian denominations to intensify their teachings on issues of morality. The paper contributes to the discussion on maintaining ethical and moral values in the Church and Society.